Perancangan User Experience Aplikasi Pemantauan Kualitas dan Kuantitas Air Sungai Brantas berbasis Website dengan Metode Design Thinking (Studi Kasus: DLH Kota Batu) - Ryan Sutawijaya; Hanifah Muslimah Az-Zahra; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Batu City is an area that is administratively located in the Upper Brantas River Basin Area (DAS). This is one of the main problems for the Batu City Environmental Service (DLH Batu) because the Water Quality Index in Batu city is light polluted with a value of 50<x<70 caused by garbage, livestock waste, and built-up areas and land conversion. Apart from that DLH Batu is still monitoring water manually, this has many drawbacks, such as requiring a long time, high costs, and the distance between the monitoring location and the analysis laboratory. Through these problems, a user experience design application for monitoring the quality and quantity of Brantas river water for DLH Batu is carried out using the design thinking method, design thinking aims to get creative and innovative solutions with the user as the center of innovation. The final result of this research is a high-fidelity prototype that is tested using usability testing for the main prospective users, namely DLH Batu as the admin and the general public as users. In testing the effectiveness aspect, admin respondents get a 100% success rate. and user respondents get a score of 95%. The efficiency aspect uses time-based efficiency calculations and the results are 0.009 goals/sec for admin respondents and 1.096 for 5 user respondents. In terms of the level of user satisfaction, the System Usability Scale (SUS) method will be used and a result of 90 for admin respondents will be included in the grade A category with an excellent rating adjective. Whereas users get a score of 70.625 and this score is included in the grade B category with an adjective rating of good.